Exploring the supply and demand factors of varietal turnover in Indian wheat - Krishna, Vijesh V.; Spielman, David J.; Veettil, Prakashan C. (Cambridge University Press, 2016)
Cultivar depreciation – the gradual decline in relative advantage of a cultivated variety over time – accentuates the vulnerability of resource-poor farmers to production risks. The current paper addresses constraints in combating cultivar depreciation of wheat in India. National level data on quoted demand for breeder seeds and breeder seed production indicated a slowdown in the rate of cultivar turnover of wheat, with average varietal age increasing from 9 years in 1997 to 12 years in 2009. Analysis of cultivar adoption patterns among farmer households of Haryana State also indicates that farmers prefer cultivars that were released a decade ago over the recent ones. Cultivar turnover rates are found to be particularly low among marginal farmers. While the structure of India's wheat breeding and seed delivery systems might be the primary cause of slow cultivar turnover, a number of social and economic factors at the micro-level are also responsible. Many of the constraints to technology adoption and wheat productivity growth, identified during the Green Revolution era, persist even today.